Pendidikan Islam Andalusia: Sebuah Kajian Sosial-Historis Pendidikan Islam Masa Kejayaan Andalusia - Aziz, Abdul; Munawar, Tri Huda (JOIES (Journal of Islamic Education Studies), 2017)
The heyday of Islam in the plains of Europe cannot be separated from a city located in the Southwest of the European Continent, Andalusia. In its heyday, the city gave birth to many influential figures with monumental works that were used as references by Muslims in their time and the world at large. The existence of strong figures and monumental works would not have been possible without an established education system in preparing them. This article uses content analysis to analyze the Islamic education system in Andalusia. The author uses the social history approach as study material. The source of the data used comes from the literature such as books, journals and so forth. The purpose of writing this article is to find out the Islamic education system in the heyday of Andalusia and the underlying factors. The results of the analysis of this paper conclude that the Islamic education system in Andalusia at the beginning was still limited to halaqah which discusses Islamic studies. Gradually, this system evolved into the kuttab system, which is the schools around the mosque, which were the forerunners of the establishment of Ma'had Aly. There are many factors that underlie the success of Islamic education in Andalusia at that time. Among these are tolerance between religious communities, cultural assimilation, equal rights and democracy, an established economy, government politics and academic collisions between the east represented by Baghdad and the west represented by Andalusia.